Investigation of the effect of a solution of lime powder on urinary calcium oxalate kidney stone risk factors in artificial and real urines : in vitro and in vivo studies - Bvumbi, Mpelegeng Victoria (University of Cape Town, 2016)
INTRODUCTION: Dietary factors in the form of citrus juices (e.g orange, grapefruits, cranberry, lemonade and lime) appear to affect the ability of urine to inhibit calcium oxalate crystallization. In South Africa, previous studies have demonstrated that black and white individuals respond differently to lithogenic and antilithogenic dietary supplements. OBJECTIVES: The current project was undertaken to study the inhibitory activity of lime in artificial urine and in the real urine of South African black and white subjects and also to assess the effects on urinary risk factors in these subjects after its ingestion. SUBJECTS AND METHODS: Experiments commenced with the preparation of artificial urine (AU) in which the effects of lime solutions (0.125-1.00 mglml) were tested by carrying out various crystallization experiments. These included the determination of the calcium oxalate (CaOx) metastable limit (MSL); particle volume-size distribution (PSD), nucleation, aggregation and growth assays. Crystal deposition was studied using scanning electron microscopy (SEM). In vitro experiments were then conducted in 24 hour urine samples from healthy South African black (n = 5) and white males (n = 5). The above-mentioned crystallization experiments were repeated in these urines. In addition, free Ca²⁺ values and the Bonn risk index (BRI) of CaOx crystallization were determined. Thereafter, a trial study in which 5 black and 4 white subjects ingested solutions of lime powder for 7 days was conducted. 24 hour urine samples were collected by subjects before and after the ingestion of lime. Urines were analysed for pH, sodium, potassium, calcium, oxalate, citrate, uric acid chloride, magnesium, phosphate, and creatinine. Urine composition values were used as input data for the calculation of relative supersaturation (RS) values for calcium oxalate monohydrate (COM), calcium oxalate dihydrate (COD), brushite and uric acid using the computer programme EQUIL and Tiselius Risk Index (TRI) was also determined. The above-mentioned CaOx crystallization experiments were also performed. Urine compositions, crystallization data and physicochemical risk indices were analyzed statistically using analysis of variance (ANOVA). RESULTS: None of the lime solutions did affect the CaOx MSL of the AU or the real urine (in vitro). However CaOx crystal nucleation was promoted while CaOx crystal growth and aggregation were inhibited. In the trial study, after ingestion of lime solutions, significant increases in urinary magnesium (1.80 vs 2.75 mmol/24h, p = 0.0001) and phosphate (20.9 vs 24.6 mmol/24h, p = 0.023) were observed in black subjects. On the other hand, in white subjects, a significant decrease in urinary oxalate (0.313 vs 0.205 mmol/24h, p = 0.023) and TRI (304 vs 187, p = 0.0102) were noted. However, lime did not increase citrate levels to a significant degree in either group. CONCLUSIONS: The results presented in this dissertation have shown that lime may be regarded as a potential therapeutic agent for reducing the risk of CaOx kidney stones in the white group based on the trial study. The results also provide further evidence in support of the hypothesis that there is a difference between the black and white populations with respect to their handling of lithogenic and antilithogenic dietary challenges. However, rigorous controlled trials in healthy subjects and in kidney stone patients need to be conducted in future studies to explicitly confirm these findings.